Employment behaviour in slack and tight labour markets - Qaisar Farooq Akram; Ragnar Nymoen (University of Oslo, Department of Economics, 2001)
Empirical and theoretical studies suggest that employment behaviour varies with the state of the labour market since hiring and firings costs depend on the availability of labour. Extending earlier empirical work on this subject, we test for state dependence in employment adjustment and in the effects of forcing variables such as indicators of aggregate demand. We also test whether anticipated labour shortage leads to multiple equilibria in (un)employment. In the inquiry, we employ a linear vector equilibrium correction model (VEqCM) and two states Markov switching VEqCMs. The models are based on quarterly data for Norwegian industry employment and aggregate unemployment in the period 1974ó96. We find clear evidence of state dependent adjustment and response to changes in forcing variables. Yet equilibrium solutions for the employment and unemployment appear invariant to cyclical and structural changes in the sample. Shifts in long run means of the variables are shown to depend on exogenous factors, product demand and unit labour costs in particular.
Keywords: E24; J32; E32; C32; E51; 330; adjustment costs; asymmetric response; multiple equilibria; cointegration; Markov switching; Arbeitsmarkt; Beschäftigung; Anpassungskosten; Norwegen